We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
89
1
avatar+472 

Given f(x)=2x^2−3 and g(x)=x+4 .

What is (fg)(x) ?

 

−2x^2+x+7

2x^3−12

2x^3+8x^2−3x−12

2x^2+x+1

 Mar 11, 2019
 #1
avatar+101161 
+2

(fg)(x)  =  f(x) * g(x) =

 

(2x^2 - 3) ( x + 4) =

 

2x^3  + 8x^2 - 3x - 12  

 

 

cool cool cool

 Mar 11, 2019

4 Online Users

avatar